The product of ORF O located within the domain of herpes simplex virus 1 genome transcribed during latent infection binds to and inhibits in vitro binding of infected cell protein 4 to its cognate DNA site - Randall, Glenn (The National Academy of Sciences of the USA, 1997)
The partially overlapping ORF P and ORF O are located within the domains of the herpes simplex virus 1 genome transcribed during latency. Earlier studies have shown that ORF P is repressed by infected cell protein 4 (ICP4), the major viral regulatory protein, binding to its cognate site at the transcription initiation site of ORF P. The ORF P protein binds to p32, a component of the ASF/SF2 alternate splicing factors; in cells infected with a recombinant virus in which ORF P was derepressed there was a significant decrease in the expression of products of key regulatory genes containing introns. We report that (i) the expression of ORF O is repressed during productive infection by the same mechanism as that determining the expression of ORF P; (ii) in cells infected at the nonpermissive temperature for ICP4, ORF O protein is made in significantly lower amounts than the ORF P protein; (iii) the results of insertion of a sequence encoding 20 amino acids between the putative initiator methionine codons of ORF O and ORF P suggest that ORF O initiates at the methionine codon of ORF P and that the synthesis of ORF O results from frameshift or editing of its RNA; and (iv) glutathione S-transferase–ORF O fusion protein bound specifically ICP4 and precluded its binding to its cognate site on DNA in vitro. These and earlier results indicate that ORF P and ORF O together have the capacity to reduce the synthesis or block the expression of regulatory proteins essential for viral replication in productive infection.